Mifologija derev’ev v tradicionnoj kul’ture slavjan: leščina (Corylus avellana) Die Mythologie der Bäume in der traditionellen Kultur der Slawen: Corylus avellana - Tatjana Agapkina (Studia Mythologica Slavica, 2015)
The author analyses the mythology of the nut tree (Corylus avallana) in the context of other Slavic ethnodendrological systems.